The Regulation of Peace River : a Case Study for River Management. - Church, Michael (Wiley, 2014)
This book presents a comprehensive overview of the first longitudinal study of the downstream response of a major river to the establishment of a large hydropower facility and dams. Peace River, a northward flowing boreal river in northwestern Canada was dammed in 1967 and the book describes the morphological response of the 1200 km downstream channel and the response of riparian vegetation to the change in flow regime over the first forty years of regulated flows. Beginning with a description of the effect of regulation on the flow and sediment regimes of the river, the book proceeds to stud.